Preparation method and application of In2O3 / g-C3N5 heterojunction material
By preparing In2O3/g-C3N5 heterojunction material, its dislocation energy band structure promotes the separation of photogenerated carriers, the problem of high electron-hole pair recombination rate in existing semiconductor photocatalytic materials is solved, and the photocatalytic activity is significantly improved and the efficient degradation of environmental pollutants is achieved.
Patent Information
- Application Number
- CN202411857400.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-17
- Publication Date
- 2025-03-21
- Estimated Expiration
- 2044-12-17
AI Technical Summary
The existing semiconductor photocatalytic materials have the problem of rapid recombination of electron-hole pairs in photocatalytic reactions, which limits their photocatalytic activity.
By using hydrothermal method and high-temperature calcination, the In2O3/g-C3N5 heterojunction material was prepared, and the dislocation band structure between In2O3 and g-C3N5 was used to form a heterojunction, which promoted the efficient separation of photogenerated electrons and holes.
It significantly improves photocatalytic activity, especially in removing environmental pollutants such as rhodamine B, methylene blue, methyl orange, etc., which show efficient degradation capabilities.
Smart Images

Figure CN119303613B_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of heterojunction photocatalytic materials, and specifically relates to a preparation method and application of an In2O3 / g-C3N5 heterojunction material. Background Art
[0002] With the rapid development of human civilization, problems such as the global energy crisis and environmental pollution have gradually emerged. Green energy technology has become an urgent need to reduce the use of fossil fuels and reduce the generation of pollutants. Photocatalytic technology is considered to have great potential because it can directly utilize solar energy. It can be applied to water decomposition to produce hydrogen, CO2 reduction, degradation of organic pollutants, and promotion of organic synthesis. Photocatalysts are the core of photocatalytic technology, and many semiconductor materials such as TiO2, CdS, ZnO, BiVO4, and g-C3N4 can be used as photocatalysts. However, single semiconductor materials have some disadvantages, such as the photogenerated electron-hole pairs tend to recombine quickly instead of participating in the photocatalytic reaction, which limits their photocatalytic activity.
[0003] In order to inhibit the recombination of electron-hole pairs and improve the photocatalytic activity, constructing heterojunction photocatalytic materials has become a promising method. Heterojunction photocatalytic materials can be divided into type II heterojunction, Schottky type heterojunction, Z type heterojunction and S type heterojunction according to the energy band structure of adjacent materials. These heterojunction materials can effectively inhibit the recombination of electron-hole pairs and improve the overall photocatalytic activity of the material, becoming an important branch of the photocatalyst family.
[0004] In2O3 (indium oxide) is an n-type semiconductor material that shows great application potential in the field of photocatalysis due to its unique electronic structure and optical properties. In2O3 has high electron mobility and good visible light response, which enables it to effectively transport electrons during the photocatalytic process, thereby improving the photocatalytic efficiency. However, In2O3 itself also has some limitations, such as the high recombination rate of photogenerated electron-hole pairs, which limits its photocatalytic performance.
[0005] In addition, carbon nitrides composed of carbon and nitrogen elements are a kind of metal-free conjugated polymer materials that have gradually attracted the attention of researchers. Among these carbon nitrides, the research on g-C3N4 two-dimensional materials is the most, and fruitful results have been achieved. However, g-C3N4 also has some inherent defects, such as its wide band gap of about 2.7 eV, which makes it only absorb visible light in a small range, and the utilization rate of sunlight is greatly reduced. It is reported that the proper adjustment of the ratio of carbon and nitrogen elements in carbon nitrides, such as increasing the nitrogen content or forming carbon vacancies, can enable the material to absorb light with lower energy, that is, to expand to the visible light region. In recent years, g-C3N5 synthesized by thermal deamination is such a new type of nitrogen-rich carbon nitride compound, which is composed of 1 triazole and 2 triazine molecules connected by azo.
[0006] The combination of In2O3 and carbon-nitrogen compounds to form heterojunction photocatalytic materials is an effective way to overcome the above defects. The research group of Professor Xue Can of Nanyang Technological University (10.1016 / j.apcatb.2013.10.029) in situ grew In2O3 nanosheets on g-C3N4 sheets, and the resulting In2O3 / g-C3N4 hybrid structure significantly improved the photocatalytic activity for H2 generation and CO2 reduction. The enhanced activity was attributed to the interfacial transfer of photogenerated electrons and holes between g-C3N4 and In2O3, resulting in effective charge separation on the two parts. The research group of Professor Liu Chunming of Taipei University of Technology (10.1016 / j.colsurfa.2024.135340) combined Co-doped In2O3 and tubular g-C3N4 to form heterojunction composite materials, and the degradation rates of tetracycline under sunlight and visible light were 100% and 90% respectively within 160 minutes. Zhu Yongfa's research group at Tsinghua University (10.1016 / j.apsusc.2019.144241) combined In2O3 and boron-doped g-C3N4 to degrade 90% of tetracycline hydrochloride within 3 hours, and also showed high photocatalytic degradation activity for NO. Similar work in Chinese patent ZL 201710891621.7, In2O3 / boron-doped g-C3N4 can degrade 97.5% of methyl orange within 120 minutes.
[0007] However, to date, there has been no report on the materials, preparation methods and applications of In2O3 and g-C3N5 composite heterojunctions.
[0008] In view of the above background and research status, the present invention is proposed. Summary of the invention
[0009] The purpose of the present invention is to provide a method for preparing an In2O3 / g-C3N5 heterojunction material, which adopts a hydrothermal method and a high-temperature calcination method, has a simple preparation process and low cost. Through the dislocated band structure between In2O3 and g-C3N5, a heterojunction is formed, a transmission space for photogenerated carriers is constructed, and efficient separation of photogenerated electrons and holes is promoted. At the same time, through the efficient visible light response characteristics of g-C3N5, the utilization rate of light by the heterojunction is expanded, and finally a significant improvement in photocatalytic activity is achieved.
[0010] Another object of the present invention is to provide an In2O3 / g-C3N5 heterojunction material for use in fields such as removal of environmental pollutants.
[0011] In order to achieve the above-mentioned purpose of the present invention, the following technical solutions are particularly adopted:
[0012] In a first aspect, the present invention provides a method for preparing an In2O3 / g-C3N5 heterojunction material, comprising the following steps: weighing indium salt, oxalic acid and sodium hydroxide, dissolving and stirring in a beaker, and then transferring them into a hydrothermal kettle for reaction; washing the obtained precipitate to remove impurities, and then drying to obtain an intermediate product; adding the intermediate product and 3-amino-1,2,4-triazole into a mortar, grinding and mixing, and then transferring them into a crucible, and placing them in a muffle furnace for roasting to obtain the In2O3 / g-C3N5 heterojunction material.
[0013] The molar ratio of the hydroxide in the sodium hydroxide to the molar ratio of the indium in the indium salt is (3-4):1.
[0014] The molar ratio of the oxalic acid to the hydroxide in the sodium hydroxide is 1:5.
[0015] The mass ratio of the intermediate product to 3-amino-1,2,4-triazole is (0.1~1):1.
[0016] The indium salt is one of nitrate, chloride and sulfate.
[0017] In some embodiments, the reaction temperature of the hydrothermal reactor is 140-180° C., and the reaction time is 24-48 hours.
[0018] In some embodiments, the calcination temperature of the muffle furnace is 500-520° C., and the calcination time is 2-4 hours.
[0019] In a second aspect, the present invention provides an application of the In2O3 / g-C3N5 heterojunction material prepared by the above-mentioned preparation method in the field of removing environmental pollutants.
[0020] The environmental pollutant includes at least one of rhodamine B, methylene blue, and methyl orange dyes.
[0021] As a preferred embodiment, a method for preparing an In2O3 / g-C3N5 heterojunction material comprises the following steps: weighing indium salt, oxalic acid and sodium hydroxide, dissolving and stirring in a beaker, and then transferring them into a hydrothermal kettle for reaction; washing the obtained precipitate to remove impurities, and then drying to obtain an intermediate product; adding the intermediate product and 3-amino-1,2,4-triazole into a mortar, grinding and mixing, and then transferring them into a crucible, and placing them in a muffle furnace for calcination to obtain the In2O3 / g-C3N5 heterojunction material.
[0022] Wherein, in this step, the molar ratio of the hydroxide ion in the sodium hydroxide to the molar ratio of the indium in the indium salt is 4:1, and the molar ratio of the hydroxide ion in the oxalic acid to the sodium hydroxide is 1:5.
[0023] Wherein, in this step, the mass ratio of the intermediate product to 3-amino-1,2,4-triazole is 0.2:1.
[0024] Wherein, in this step, the reaction temperature of the hydrothermal kettle is 180° C. and the reaction time is 24 hours.
[0025] Wherein, in this step, the roasting temperature of the muffle furnace is 520° C., and the roasting time is 3 hours.
[0026] The technical solution provided by the present invention has the following beneficial effects: the present invention adopts a hydrothermal method and a high-temperature calcination method, and the preparation process is simple and the cost is low. Through the dislocation band structure between In2O3 and g-C3N5, a heterojunction is formed, and a transmission space for photogenerated carriers is constructed, which promotes the efficient separation of photogenerated electrons and holes. At the same time, through the efficient visible light response characteristics of g-C3N5, the utilization rate of light by the heterojunction is expanded, and finally a significant improvement in photocatalytic activity is achieved, especially the efficient removal of environmental pollutants such as rhodamine B, methylene blue, methyl orange, etc. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] Figure 1 The XRD diagrams of the intermediate product and product obtained in Example 1 of the present invention and the products obtained in Comparative Examples 1 and 2 are shown.
[0028] Figure 2 This is a TEM image of the product obtained in Example 1 of the present invention. DETAILED DESCRIPTION
[0029] The technical solution of the present invention will be clearly and completely described below in conjunction with the embodiments. Obviously, the described embodiments are part of the embodiments of the present invention, rather than all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0030] The present invention is further described below by way of examples. Unless otherwise specified, the materials in the examples are prepared according to existing methods or directly purchased from the market.
[0031] The reagents and raw materials used in the present invention are shown in Table 1 below:
[0032] Table 1 Reagents and raw materials used in the present invention
[0033] Reagent name Molecular formula Specification Manufacturer (Origin) Indium nitrate <![CDATA[InN3O9.xH2O]]> Analytical grade Shanghai MacLean Biochemical Technology Co., Ltd. oxalic acid <![CDATA[C2H2O4]]> Analytical grade Sinopharm Chemical Reagent Co., Ltd. Sodium hydroxide NaOH Analytical grade Sinopharm Chemical Reagent Co., Ltd. 3-Amino-1,2,4-triazole <![CDATA[C2H4N4]]> Analytical grade Shanghai MacLean Biochemical Technology Co., Ltd. Deionized water <![CDATA[H2O]]> <![CDATA[S<5 μs·cm -1 ]]> Hangzhou Wahaha Group Co., Ltd. Example 1
[0034] Accurately weigh 0.01 mol of indium nitrate, 0.008 mol of oxalic acid, and 0.04 mol of sodium hydroxide in a 100 ml beaker, add 80 ml of deionized water, continue stirring for 30 minutes after dissolving, transfer to a 100 ml hydrothermal kettle, react at 180°C for 24 hours, wash the obtained precipitate with water and alcohol for 3 times each, and vacuum dry to obtain an intermediate product. Weigh 0.4 g of the intermediate product and 2 g of 3-amino-1,2,4-triazole, add them to a mortar, grind and mix, transfer to a crucible, and roast at 520°C in a muffle furnace for 3 hours to obtain an In2O3 / g-C3N5 heterojunction material.
[0035] 100 mg of the prepared In2O3 / g-C3N5 heterojunction material was placed in a beaker containing 100 ml of a 10 mg / L rhodamine B solution, ultrasonically treated for 2 minutes, dark adsorbed for 30 minutes, and then illuminated for 30 minutes with a 300-W xenon lamp at a distance of 20 cm from the liquid surface under stirring. The degraded solution was centrifuged and its absorbance at 554 nm was measured by a UV-visible spectrophotometer. The degradation rate of rhodamine B was calculated to be 99.3%. Example 2
[0036] Accurately weigh 0.01 mol of indium nitrate, 0.006 mol of oxalic acid, and 0.03 mol of sodium hydroxide in a 100 ml beaker, add 80 ml of deionized water, continue stirring for 30 minutes after dissolving, transfer to a 100 ml hydrothermal kettle, react at 160°C for 48 hours, wash the obtained precipitate with water and alcohol for 3 times each, and vacuum dry to obtain an intermediate product. Weigh 0.2 g of the intermediate product and 2 g of 3-amino-1,2,4-triazole, add them to a mortar, grind and mix, transfer to a crucible, and roast at 500°C in a muffle furnace for 2 hours to obtain an In2O3 / g-C3N5 heterojunction material.
[0037] 100 mg of the prepared In2O3 / g-C3N5 heterojunction material was placed in a beaker containing 100 ml of a 10 mg / L methylene blue solution, ultrasonically treated for 2 minutes, dark adsorbed for 30 minutes, and then illuminated for 30 minutes with a 300-W xenon lamp at a distance of 20 cm from the liquid surface under stirring. The degraded solution was centrifuged and its absorbance at 664 nm was measured by a UV-visible spectrophotometer. The degradation rate of methylene blue was calculated to be 93.4%. Example 3
[0038] Accurately weigh 0.01 mol of indium nitrate, 0.008 mol of oxalic acid, and 0.04 mol of sodium hydroxide in a 100 ml beaker, add 80 ml of deionized water, continue stirring for 30 minutes after dissolving, transfer to a 100 ml hydrothermal kettle, react at 180°C for 24 hours, wash the obtained precipitate with water and alcohol for 3 times each, and vacuum dry to obtain an intermediate product. Weigh 2 grams of the intermediate product and 2 grams of 3-amino-1,2,4-triazole, add them to a mortar, grind and mix, transfer to a crucible, and roast at 520°C in a muffle furnace for 3 hours to obtain an In2O3 / g-C3N5 heterojunction material.
[0039] 100 mg of the prepared In2O3 / g-C3N5 heterojunction material was placed in a beaker containing 100 ml of 10 mg / L methyl orange solution, ultrasonically treated for 2 minutes, dark adsorbed for 30 minutes, and then illuminated for 60 minutes with a 300-W xenon lamp light source at a distance of 20 cm from the liquid surface under stirring. The degraded solution was centrifuged and its absorbance at 460 nm was measured by a UV-visible spectrophotometer. The degradation rate of methyl orange was calculated to be 85.6%. Example 4
[0040] Accurately weigh 0.01 mol of indium nitrate, 0.008 mol of oxalic acid, and 0.04 mol of sodium hydroxide in a 100 ml beaker, add 80 ml of deionized water, continue stirring for 30 minutes after dissolving, transfer to a 100 ml hydrothermal kettle, react at 180°C for 24 hours, wash the obtained precipitate with water and alcohol for 3 times each, and vacuum dry to obtain an intermediate product. Weigh 0.4 g of the intermediate product and 2 g of 3-amino-1,2,4-triazole, add them to a mortar, grind and mix, transfer to a crucible, and roast at 520°C in a muffle furnace for 3 hours to obtain an In2O3 / g-C3N5 heterojunction material.
[0041] 100 mg of the prepared In2O3 / g-C3N5 heterojunction material was placed in a beaker containing 100 ml of a 10 mg / L methylene blue solution, ultrasonically treated for 2 minutes, dark adsorbed for 30 minutes, and then illuminated for 30 minutes with a 300-W xenon lamp at a distance of 20 cm from the liquid surface under stirring. The degraded solution was centrifuged and its absorbance at 664 nm was measured by a UV-visible spectrophotometer. The degradation rate of methylene blue was calculated to be 97.3%. Example 5
[0042] Accurately weigh 0.01 mol of indium nitrate, 0.008 mol of oxalic acid, and 0.04 mol of sodium hydroxide in a 100 ml beaker, add 80 ml of deionized water, continue stirring for 30 minutes after dissolving, transfer to a 100 ml hydrothermal kettle, react at 180°C for 24 hours, wash the obtained precipitate with water and alcohol for 3 times each, and vacuum dry to obtain an intermediate product. Weigh 0.4 g of the intermediate product and 2 g of 3-amino-1,2,4-triazole, add them to a mortar, grind and mix, transfer to a crucible, and roast at 520°C in a muffle furnace for 3 hours to obtain an In2O3 / g-C3N5 heterojunction material.
[0043] 100 mg of the prepared In2O3 / g-C3N5 heterojunction material was placed in a beaker containing 100 ml of 10 mg / L methyl orange solution, ultrasonically treated for 2 minutes, dark adsorbed for 30 minutes, and then illuminated for 60 minutes with a 300-W xenon lamp light source at a distance of 20 cm from the liquid surface under stirring. The degraded solution was centrifuged and its absorbance at 460 nm was measured by a UV-visible spectrophotometer. The degradation rate of methyl orange was calculated to be 90.5%. Comparative Example 1
[0044] Accurately weigh 0.01 mol of indium nitrate, 0.008 mol of oxalic acid, and 0.04 mol of sodium hydroxide in a 100 ml beaker, add 80 ml of deionized water, continue stirring for 30 minutes after dissolving, transfer to a 100 ml hydrothermal kettle, react at 180°C for 24 hours, wash the obtained precipitate with water and alcohol for 3 times each, and vacuum dry to obtain an intermediate product. Weigh 2 grams of the intermediate product and bake it at 520°C in a muffle furnace for 3 hours to obtain In2O3 monomer.
[0045] Take 100 mg of the prepared In2O3 monomer and place it in a beaker containing 100 ml of 10 mg / L rhodamine B solution. After ultrasonic treatment for 2 minutes and dark adsorption for 30 minutes, it is illuminated by a 300-watt xenon lamp light source at a distance of 20 cm from the liquid surface for 30 minutes under stirring. After centrifugation, the degraded solution is measured by a UV-visible spectrophotometer at 554 nm. The degradation rate of rhodamine B is calculated to be 46.2%. Comparative Example 2
[0046] Accurately weigh 2 g of 3-amino-1,2,4-triazole and calcine it at 520 °C in a muffle furnace for 3 h to obtain g-C3N5 monomer.
[0047] 100 mg of the prepared g-C3N5 monomer was placed in a beaker containing 100 ml of a 10 mg / L rhodamine B solution, subjected to ultrasonic treatment for 2 minutes, dark adsorbed for 30 minutes, and then illuminated for 30 minutes with a 300-W xenon lamp at a distance of 20 cm from the liquid surface under stirring. The degraded solution was centrifuged and its absorbance at 554 nm was measured by a UV-visible spectrophotometer. The degradation rate of rhodamine B was calculated to be 55.9%. Comparative Example 3
[0048] Accurately weigh 0.01 mol of indium nitrate, 0.008 mol of oxalic acid, and 0.04 mol of sodium hydroxide in a 100 ml beaker, add 80 ml of deionized water, continue stirring for 30 minutes after dissolving, transfer to a 100 ml hydrothermal kettle, react at 180°C for 24 hours, wash the obtained precipitate with water and alcohol for 3 times each, and vacuum dry to obtain an intermediate product. Weigh 0.4 g of the intermediate product and 2 g of melamine, add them to a mortar, grind and mix, transfer to a crucible, and roast at 520°C in a muffle furnace for 3 hours to obtain an In2O3 / g-C3N4 heterojunction material.
[0049] 100 mg of the prepared In2O3 / g-C3N4 heterojunction material was placed in a beaker containing 100 ml of a 10 mg / L rhodamine B solution, ultrasonically treated for 2 minutes, dark adsorbed for 30 minutes, and then illuminated for 30 minutes with a 300-W xenon lamp at a distance of 20 cm from the liquid surface under stirring. The degraded solution was centrifuged and its absorbance at 554 nm was measured by a UV-visible spectrophotometer. The degradation rate of rhodamine B was calculated to be 85.1%.
[0050] It can be seen from Comparative Examples 1 and 2 that the degradation effect of the prepared In2O3 monomer and g-C3N5 monomer materials on Rhodamine B is significantly lower than that of the In2O3 / g-C3N5 heterojunction material under the same conditions. This is mainly because the recombination probability of photogenerated electrons and holes in the In2O3 monomer and g-C3N5 monomer materials is relatively high, and sufficient photogenerated carriers required for efficient photocatalytic reactions are not generated.
[0051] It can be seen from Comparative Example 3 that the degradation effect of In2O3 / g-C3N4 heterojunction material on Rhodamine B is significantly lower than that of In2O3 / g-C3N5 heterojunction material under the same conditions. This is mainly because the band gap of g-C3N4 is larger, which affects the effective separation of photogenerated carriers. At the same time, g-C3N5 expands the absorption range of the material for visible light and increases the utilization rate of visible light.
[0052] Characterization of In2O3 / g-C3N5 heterojunction materials
[0053] The present invention uses a D8 Advance X-ray diffractometer from Bruker Spectroscopy Instruments of Germany to perform XRD analysis on the intermediate product prepared in Example 1 of the present invention, the In2O3 / g-C3N5 heterojunction material, and the In2O3 and g-C3N5 products prepared in Comparative Example 1 and Comparative Example 2, respectively. The results are as follows: Figure 1 As shown, the test conditions are: Cu target Kα line, λ = 0.15406nm, 2θ is 10°~70°, and the scanning speed is 5(°) / min. Figure 1 The intermediate product of Example 1 is In(OH)3, and the diffraction peaks at 2θ of 22.3, 31.7, 35.6, 39.1, 45.5, 51.2, 56.5° and 66.3° respectively correspond to the (200), (220), (013), (222), (400), (420), (422) and (440) crystal planes of pure body-centered cubic phase In(OH)3 (PDF card 85-1338), and In(OH)3 has high purity and crystallinity. Figure 1 The product of comparative example 1 is In2O3, and the diffraction peaks at 2θ of 21.3, 30.6, 35.5, 51.0° and 60.6° respectively correspond to the (211), (222), (400), (440) and (662) crystal planes of In2O3 (PDF card 71-2195), the space group is la-3, a=b=c=10.117. Figure 1 The product of Comparative Example 2 is g-C3N5, and the diffraction peaks at 2θ of 12.8° and 27.5° correspond to the (100) and (002) crystal planes, respectively. In the XRD spectrum of the product of Example 1, all diffraction peaks of the product In2O3 of Comparative Example 1 and the product g-C3N5 of Comparative Example 2 can be observed, and the intensity is reduced, indicating that the product is a composite of In2O3 and g-C3N5, and retains their respective crystal structures.
[0054] The present invention uses a high-resolution field emission transmission electron microscope JEM-2100F produced by JEOL Ltd. to test the microstructure of the In2O3 / g-C3N4 heterojunction material obtained in Example 1. The obtained photograph is as follows: Figure 2 shown. Figure 2 It can be seen that the In2O3 / g-C3N5 heterojunction material is mainly composed of g-C3N5 with a lamellar structure and In2O3 with a cubic structure. The two are closely combined, which provides the possibility for the efficient transmission of photogenerated carriers.
[0055] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that the technical solutions described in the aforementioned embodiments can still be modified, or some or all of the technical features therein can be replaced by equivalents. However, these modifications or replacements do not make the essence of the corresponding technical solutions deviate from the scope of the technical solutions of the embodiments of the present invention.
Claims
1. A method for preparing an In2O3 / g-C3N5 heterojunction material, characterized in that: The invention comprises the following steps: weighing indium salt, oxalic acid and sodium hydroxide, dissolving and stirring in a beaker, and then transferring to a hydrothermal kettle for reaction; washing the obtained precipitate to remove impurities, and then drying to obtain an intermediate product; adding the intermediate product and 3-amino-1,2,4-triazole into a mortar, grinding and mixing, and then transferring to a crucible; and placing the mixture in a muffle furnace for roasting to obtain an In2O3 / g-C3N5 heterojunction material, wherein the molar ratio of the number of hydroxide in the sodium hydroxide to the molar number of indium in the indium salt is (3-4):1, the molar ratio of the hydroxide in the oxalic acid to the sodium hydroxide is 1:5, the mass ratio of the intermediate product to 3-amino-1,2,4-triazole is (0.1-1):1, the reaction temperature of the hydrothermal kettle is 140-180°C, the reaction time is 24-48 hours, the roasting temperature of the muffle furnace is 500-520°C, and the roasting time is 2-4 hours.
2. The preparation method according to claim 1, characterized in that: The indium salt is one of nitrate, chloride and sulfate.
3. Use of an In2O3 / g-C3N5 heterojunction material obtained by the preparation method described in any one of claims 1 to 2 in removing environmental pollutants.
4. The use according to claim 3, characterized in that: The environmental pollutant includes at least one of rhodamine B, methylene blue, and methyl orange dyes.
Citation Information
Patent Citations
Preparation and application of photocatalysts In2O3 / g-C3N4B
CN107790163A
Cadmium sulfide / indium oxide / phosphorus oxide doped carbon nitride ternary composite material as well as preparation method and application thereof
CN114602528A